Effectiveness of portfolio assessment in primary education: A multi-complementary research approach - Dogan, Yunus; Yildirim, Nazife Tugba; Batdi, Veli (Pergamon-Elsevier Science Ltd, 2024)
The current study represents a comprehensive exploration of the efficacy of portfolio assessment within primary school contexts, employing a Multi-Complementary Research (McA) framework comprising three distinct stages. In the pre-complementary knowledge stage, data collection commenced utilizing the document analysis method, concurrently conducting meta -analysis and meta-thematic analysis. From 18 studies, a meta -analysis of 23 datasets revealed a medium-level overall effect size. Simultaneously, meta-thematic analysis was conducted on 6 studies meeting specific inclusion criteria, analyzing themes and codes through content analysis. Transitioning to the post-complementary knowledge stage, an experimental study employing a pretest-posttest control group design was undertaken with third-grade primary school students. Additionally, thematic analysis based on participant perspectives was conducted. Subsequently, an eventual complementary knowledge stage was achieved by synthesizing findings from the initial two stages. Key themes emerged, titled the effect of portfolio use in primary education on academic success, 21st century skills, and attitudes. The collective findings indicate that portfolio assessment in primary schools yields positive effects across all three identified themes.
Keywords: Multi-complementary research approach; Meta-thematic analysis; Meta-analysis; Portfolio; Assessment